Studies on cultural, morphological, pathogenic and molecular variability of Alternaria brassicae, the causal agent of blight disease of rapeseed-mustard - Prateeksha Mehra,; AK Tewari,; GoharTaj, (Journal of Oilseed Brassica, 2026)
In India, rapeseed-mustard is one of the most edible oilseed crops after groundnut and contributes around 26.1per cent of the total oilseed production. Among Brassica oil seed crops, Indian mustard [Brassica juncea (L.)Czern & Coss.] is commonly cultivated in most of the Indian states. Alternaria blight disease caused by A.brassicae has been reported from all the continents of the world causing up to 47 per cent yield losses with noproven source of resistance. The present investigation was carried out to study the cultural, morphological,pathogenic and molecular variability among A. brassiace isolates collected from different Brassica spp.(Pantnagar) and from different geographical locations of India (Karnal, Punjab, Bihar, Jammu and Kangra) toexploit them in breeding programme during screening for resistance sources and selection of host differentials.In the present studies A. brassicae isolates (20 nos.) showed the existence of genetic diversity. Significantvariation in cultural, morphological, pathogenic and molecular variability was observed in A. brassiace isolatesirrespective to geographical locations and Brassica spp. Maximum radial growth (82.0 mm) was in AB-B.juncea Pantnagar isolate, while minimum in AB- B. caulorapa (49.7 mm) on PDA. Variations were alsoobserved in colony colour, appearance, margin and zonation number. Substantial variations were found in sporemorphology in respect to conidial length, width and number of septa. Average conidial length and width werevaried from 29.0-6.6 x 185.3-28.2μm. Maximum spore length and width was in AB-B. carinata isolate (185.3x 25.6 μm), while minimum in AB-B. caulorapa (29.0 x 6.6μm). Number of horizontal and vertical septa rangedbetween 3.50-14.75 and 0.75-5.0 respectively. All the isolates were pathogenic to Brassica spp. AB-B. junceaPantnagar isolate was most virulent, while AB-S. alba least virulent. RAPD (18 no.) and ISSR (4 no.) primersgenerated a total of 310 reproducible and scorable polymorphic bands ranged from 100 to 1350 bp whichdisplayed genetic polymorphisms among the A. brassicae isolates. On the basis of cultural, morphological,pathogenic and molecular variability, the A. brassiace isolates has been categorized into 5 major groups. GroupI: AB-R. sativus, AB-B. pekinensis, AB-B. oleracea, AB-B. botrytis and AB-B. caulorapa; Group II: ABB.juncea Pantnagar, AB-Yellow sarson, AB-Toria, AB-B. nigra, AB-R. oleifera, AB-B. juncea Karnal, ABB.juncea Punjab and AB-B. juncea Bihar; Group III: AB-B. napus, AB-B. carinata, AB-E. sativa , AB-S.alba; Group IV: AB-B. juncea Kangara and AB-B. juncea Jammu; Group V: AB-B. rugosa. The differentBrassica spp. (08 nos.) used in the present investigation to differentiate different A. brassicae isolates (09 nos.)as host differentials has been categorized into 4 major groups on the basis of differential phenotypic diseasereactions. Group I: Varuna, PT-303, PYS-6 and B. nigra; Group II: PBN-9501 and Kiran; Group III: E.sativa; Group IV: S. alba. Among different methods of culture preservation of A. brassicae isolates, 10 percent glycerol at -20ºC was best in terms of sporulation (66.7%) followed by PDA at 4ºC (65.7%) and could beused for the preservation of A. brassicae isolates at least two years.